1991
DOI: 10.1007/bf00201830
|View full text |Cite
|
Sign up to set email alerts
|

Selection of DNA sequences from interval 6 of the human Y chromosome with homology to a Y chromosomal fertility gene sequence of Drosophila hydei

Abstract: An experimental approach towards the molecular analysis of the male fertility function, located in interval 6 of the human Y chromosome, is presented. This approach is not based on the knowledge of any gene product but on the assumption that the functional DNA structure of male fertility genes, evolutionary conserved with their position on the Y chromosome, may contain an evolutionary conserved frame structure or at least conserved sequence elements. We tested this hypothesis by using dhMiF1, a fertility gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…DXYS14 (Cooke et al 1985), DXYS15, DXYS17 (Simmler et al 1987), DXYS20 and DXYS28 (Page et al 1987). Simple sequence families, such as (Ca)n (Vogt et al 1989) and (gata), (Arnemann et al 1986) have also been identified on Yp, but their degree of variability has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…DXYS14 (Cooke et al 1985), DXYS15, DXYS17 (Simmler et al 1987), DXYS20 and DXYS28 (Page et al 1987). Simple sequence families, such as (Ca)n (Vogt et al 1989) and (gata), (Arnemann et al 1986) have also been identified on Yp, but their degree of variability has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Y6BSt64. and Y6BS65 (Vogt et al, 1991). T he 25 PC R prim ers o f the sY prim er fam ily (V ollrath et al, 1992) w ere selected w ith regard to their reliability in m ultiplex PCR experim ents as described by H enegariu et al (1994) and their position in Y q l l .…”
Section: Dna Probes and S Y Primersmentioning
confidence: 99%
“…1990). H ybridizations w ere carried out in heparin buffer u n d e r the co n d itio n s described by Vogt et al (1991).…”
Section: Dna Preparation and Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both amplicons contain significant homology regions to a germ cell-specific transcript ( dhMiF1 ) expressed on the lampbrush loops of the Y chromosome of D. hydei and designated earlier as the pYH6 sequence family [43] . Their major sequence cluster (pY6H14, pYH34, pYH54, pYH64, pYH65) was found on both arms of the P4 palindrome [Keil et al, unpubl.…”
Section: Impairment Of Dynamic Azoospermia Factor Chromosome Structurmentioning
confidence: 99%